2009
DOI: 10.1016/j.gaceta.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en el uso de la terapia hormonal sustitutiva tras una intervención informativa dirigida a mujeres y prescriptores

Abstract: Systematic and independent educational interventions aimed at women in the general population and prescribers are both effective and necessary. The HRT epidemic and its health costs, as well as the shift to tibolone prescription and the adverse effects of this drug, should be investigated nationwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Studies for another group of medicines have found that following a health safety warning for such medicines, pharmaceutical companies’ promotion for such medicines did not cease and also their advertising campaigns continued trying to increase sales, including via medical associations. 29 For example, it has been found that when clinical trials were published with negative results for hormone replacement therapy (HRT), since they presented certain adverse effects, 30 some scientific societies provided information that was trying to counteract the information of such clinical trials and saying that prescribing of HRT should not change by such clinical trials, 31 and has been known that pharmaceutical companies had secretly briefed medical societies on HRT 32 and had used medical associations in order to promote HRT. 33 Studies are needed to ascertain whether something similar happened with rosiglitazone and how promotion evolved after safety warnings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies for another group of medicines have found that following a health safety warning for such medicines, pharmaceutical companies’ promotion for such medicines did not cease and also their advertising campaigns continued trying to increase sales, including via medical associations. 29 For example, it has been found that when clinical trials were published with negative results for hormone replacement therapy (HRT), since they presented certain adverse effects, 30 some scientific societies provided information that was trying to counteract the information of such clinical trials and saying that prescribing of HRT should not change by such clinical trials, 31 and has been known that pharmaceutical companies had secretly briefed medical societies on HRT 32 and had used medical associations in order to promote HRT. 33 Studies are needed to ascertain whether something similar happened with rosiglitazone and how promotion evolved after safety warnings.…”
Section: Discussionmentioning
confidence: 99%
“…El intervencionismo médico a través de los controles sanitarios Sánchez (2012) desarrolla varios ejemplos referidos tanto a tratamientos médicos como a los controles sanitarios que una mujer no necesita, entre los que se encuentran los cribados de cáncer de mama y de cérvix, el tratamiento de la osteoporosis, la vacuna del VPH y la terapia hormonal sustitutiva (THS). Respecto a este último tratamiento, la médica Carmen Mosquera (2009) indica que antes del comunicado de la Agencia Española del Medicamento en el 2004, que recogía los resultados de las investigaciones científicas que alertaban de las enfermedades que generaba este tratamiento (cáncer de mama, cáncer de endometrio, infarto de miocardio, enfermedad vascular cerebral y tromboembolia venosa), se estimaba que un 17 % de las mujeres asturianas usaban estos compuestos hormonales. Posteriormente, con la iniciativa de difundir este comunicado tanto entre profesionales como mujeres, se observó un descenso del 73,6 %.…”
Section: El Intervencionismo En La Alimentaciónunclassified